THE ROLE OF SUBJECT (MUJTAHID) IN AL-SHAFI'I'S METHODOLOGY: HERMENEUTIC APPROACH (American Journal of Islam and Society, 1997)
Ever since the Qur'an was revealed, Muslims have been making greatefforts to understand and live in accordance with it. Within a very shortperiod of time after the Prophet's death, schools of fish emerged in theHijaz, Iraq, and Syria. They defined the sources of the religion (al-din)and engaged in developing methods to better understand them. By theearly part of the second century, more systematic approaches appeared;the roots of the schools that emerged reached back to the Companions ofthe Prophet as well as to the Prophet himself.' Their approaches representedman's natural tendencies to understanding the din. Many schoolsappeared only to fade away and be replaced by ones more comprehensivein their approach. In the late second century, Imam al-Shafi'i (150-204 A.H.) put forward the first systematic methodology of fiqh. In hiswork, al-Risalah, Imam al-Shafi'i offered a methodoIogy for the verypurpose of understanding the din. Of course, the methodology took forgranted a certain definition of Islam. Even though his methodology drewfrom prior lines of thought, it is widely accepted that as an originalmethodology, the Imam's theory of fiqh drastically transformed the perceptionof Islam that had hitherto prevailed."In order to change the approach toward the din, he redefined conceptssuch as Sunnah and ijtihad. He identified ijtihad with qiyas; and whereasthe term Sunnah had been used for the practice of the Muslim community,the Imam restricted its application to the Sunnah of the Prophetand the companions. In his vocabulary the concept of hikmah took onconsiderable importance. Al-Shafi'i can almost be singled out by his definitionof the concept of hikmah from other Muslim scholars. In order toestablish and consolidate the authority of the Sunnah on the basis of theQur'an, he interpreted and defined this Qur'anic concept as being synonymouswith the Sunnah ...